Convenient Synthesis of 1,4-Dideoxy-1,4-imino-D-ribitol from D-Ribose - Makoto Oba; Shoi Kawaji; Hironobu Kushima; Takanori Sano; Kozaburo Nishiyama (Journal of Chemistry)
This paper describes a convenient synthesis of 1,4-dideoxy-1,4-imino-D-ribitol (DRB) from D-ribose. L-Lyxonolactone, a key intermediate in this synthesis, was prepared by base-promoted hydrolysis of a 5-chlorinated D-ribonolactone derivative with inversion of configuration at the C-4 position. Cyclization of the generated dimesylated L-lyxitol with benzylamine proceeded with another configurational inversion at C-4 to afford the D-ribo-configured pyrrolidine system, which upon deprotection gave DRB.